Pengaruh Kecerdasan Emosional, Kecerdasan Intelektual, Kecerdasan Spiritual, Kecerdasan Sosial dan Perilaku Belajar Terhadap Tingkat Pemahaman Akuntansi - Paskah Ika Nugroho; Monica Cahyaningtyas (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
This study examines how much influence emotional quotients, intelligence quotients, spiritual quotients, social intelligence and learning behavior have on the understanding of accounting level and see whether there are differences in there are any differences to those factors and understanding of accounting level between male and female students. The SWCU Economics and Business Faculty accounting students were used as research objects. This research is quantitative research, with a sampling technique used purposive sampling and collecting 94 students who passed 10 conditional courses (PBMt) as respondents. Data was collected by submitting questionnaire which was distributed via email. Multiple linear regression test and Independent Sample t Test were used to analyze the data. The result of the study showed that emotional quotients, intelligence quotients, spiritual quotients have a positive influence on the level of accounting understanding, while social intelligence and learning behavior have a negative influence on the level of accounting understanding. This study also proves that there are only differences in emotional intelligence between male and female students.